Crystallinity of commercial carbon fibers from X-ray diffraction (XRD) studies - Indra Neel Pulidindi (International Journal of Photochemistry and Photochemical Research, 2024)
Sized carbon fibers have commercial significance. Such carbon fibers serves has excellent reinforcing material with the polymer resin filler matrix leading to the formation of carbon fiber reinforced composites (CFRCs). Polarized carbon fibers find applications in the realms of health, energy, environment, defence, catalysis and smart materials. For brevities sake, the focus of the current research paper is only on the structural characterization of carbon fibers using XRD. The structure of the pitch derived (NX90, NX100) and polyacrylonitrile, PAN, (T700SC) derived sized commercial carbon fibers (CFs) were analysed using X-ray diffraction (XRD) technique. The inter layer spacing (d002) of NX90, NX100, T700SC and graphite was 0.3388, 0.3395, 0.3514 and 0.3350 respectively. Likewise, the average crystallite size values along the c-axis for NX90, NX100, T700SC and graphite were 14.10, 14.26, 1.33, and 0.06708 nm respectively while the average crystallite sizes along a-axis for NX90, NX100, T700SC and graphite were 29.16, 29.25, 2.75, 0.2461 nm respectively. Thus Pitch based carbon fibers (NX90, NX100) exhibited polycrystalline graphitic structure while polyacrylonitrile (PAN) based fibers (T700SC) have turbostratic graphitic carbon structure. Such changes in structure will have implications on the performance of CFRPs ultimately produced using the carbon fibers reported here.
Keywords: Carbon fibers; Structure; XRD; characterization; crystallinity; pitch; polyacrylonitrile